2009
DOI: 10.1364/oe.17.004134
|View full text |Cite
|
Sign up to set email alerts
|

Impact of enhanced resolution, speed and penetration on three-dimensional retinal optical coherence tomography

Abstract: : Recent substantial developments in light source and detector technology have initiated a paradigm shift in retinal optical coherence tomography (OCT) performance. Broad bandwidth light sources in the 800 nm and 1060 nm wavelength region enable axial OCT resolutions of 2-3 mum and 5-7 mum, respectively. Novel high speed silicon based CMOS cameras at 800 nm and InGaAs based CCD cameras in combination with frequency domain OCT technology enable data acquisition speeds of up to 47,000 A-scans/s at 1060 nm and up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
49
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 42 publications
3
49
0
1
Order By: Relevance
“…It is known that these computed imaging techniques are more sensitive to motion along the slow axis [15] and also that motion is more difficult to correct along the slow axis due to missing information [1,2]. Therefore, the amplitude of motion along the slow axis was kept smaller (~9.4 µm) while the fast-axis motion was kept the same (~14.7 µm).…”
Section: Phantom Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that these computed imaging techniques are more sensitive to motion along the slow axis [15] and also that motion is more difficult to correct along the slow axis due to missing information [1,2]. Therefore, the amplitude of motion along the slow axis was kept smaller (~9.4 µm) while the fast-axis motion was kept the same (~14.7 µm).…”
Section: Phantom Resultsmentioning
confidence: 99%
“…Motion in tissues has always been problematic for in vivo imaging in high-resolution optical systems [1][2][3]. From retinal to cardiac movements, these involuntary motions make it difficult to acquire and process artifact-free in vivo data.…”
Section: Introductionmentioning
confidence: 99%
“…This may limit imaging speed for some medical and biological applications which have a limited permitted sample exposure, see e.g. the discussions in [9,119]. However, it can be shown that even for sensitive application.…”
Section: Basicsmentioning
confidence: 99%
“…Image-degrading motion artifacts are inevitable for many samples such as the human retina [119]. Complex hardware and numerical correction schemes have been employed [166], but they are difficult to implement and need to be tailored to the specific application.…”
Section: Applicationsmentioning
confidence: 99%
“…SD-OCT in the 800 nm region currently outperforms SS-OCT in terms of resolution due to the availability of broadband lasers. Also SD-OCT now achieves ultra high-speed, comparable to the fastest available SS-OCT systems due to advances in camera technology [16][17][18]. However, SD-OCT requires a significant amount of signal processing for background handling and resampling.…”
Section: Biophotonicsmentioning
confidence: 99%